Propofol + Granisetron vs. Propofol + Metoclopramide in Symptom Management of Acute Migraine Headache; a Double-Blind Randomized Clinical Trial - Abiri, Samaneh; Chegin, Mehdi; Soleimani, Reza; Hatami, Naser; Kalani, Navid; Rayatdoost, Esmail (Archives of Academic Emergency Medicine, 2022)
Introduction: Acute headache is one of the most common reasons for emergency department (ED) visits. This study aimed to compare the combination of propofol and granisetron with propofol and metoclopramide in symptom management of acute migraine headache. Methods: In this double-blind randomized clinical trial, 60 adult patients with acute migraine headache who referred to ED were randomly divided into two groups of propofol + metoclopramide and propofol + granisetron. Pain and nausea/vomiting severity as well as blood pressure were compared between groups 30, 45, and 60 minutes after treatment. Results: The two groups had similar situation regarding mean age (p = 0.606), sex distribution (p = 0.793), baseline severity of pain (p = 0.642), frequency of nausea/vomiting (p = 0.488), and vital signs (p > 0.05). The severity of pain was similar in the two groups 30 (p = 0.731), 45 (p = 0.460), and 60 (p = 0.712) minutes after treatment. The number of patients with resistant nausea and vomiting 60 minutes after treatment was significantly higher in metoclopramide group (30.0% versus 10.0%; p = 0.033). Diastolic pressure 60 minutes after treatment (81.43 ±8.94 vs. 74.97 ± 4.8; p = 0.001) and heart rate 30 minutes after treatment (68.87 ±6.52 vs. 73.57± 7.62; p = 0.013) had statistically significant differences between the groups. Conclusion: The combination of propofol and granisetron was superior to propofol and metoclopramide in case of controlling nausea and vomiting of cases with acute migraine headache; meanwhile, no differences were observed in case of pain relief and hemodynamic status between the two groups.